2016
DOI: 10.1016/j.epsl.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical evolution of interlocked rough slip surfaces: The role of normal stress

Abstract: International audienceWe study the evolution of slip surface topography using direct shear tests of perfectly mating surfaces. The tests are performed under imposed constant normal stress and constant slip rate conditions, to a sliding distance comparable to the roughness scale of the studied surfaces. Prismatic limestone blocks are fractured in tension using four-point bending and the generated surface topographies are measured using a laser profilometer. The initially rough fracture interfaces are tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 43 publications
2
18
1
Order By: Relevance
“…On the whole, the behavior observed in the simulations is consistent with the classical picture of adhesive wear hypothesized from experimental observations (21)(22)(23)(24). Recent small-scale wear experiments on ceramics and rocks (25,26) confirm the formation of cylindrical and spherical wear debris particles. We make the distinction that this work is focused on wear by fracture-induced debris formation, as opposed to surface folding and delamination (23) mechanisms that may occur at different scales and/or under different wear conditions, e.g., abrasive wear.…”
Section: Significancesupporting
confidence: 75%
See 1 more Smart Citation
“…On the whole, the behavior observed in the simulations is consistent with the classical picture of adhesive wear hypothesized from experimental observations (21)(22)(23)(24). Recent small-scale wear experiments on ceramics and rocks (25,26) confirm the formation of cylindrical and spherical wear debris particles. We make the distinction that this work is focused on wear by fracture-induced debris formation, as opposed to surface folding and delamination (23) mechanisms that may occur at different scales and/or under different wear conditions, e.g., abrasive wear.…”
Section: Significancesupporting
confidence: 75%
“…Inspired by (i) our recent study (19) that revealed the critical importance of the junction shear strength (τ ) on debris particle formation and (ii) macroscopic laboratory observations of a linear correlation between the tangential work and wear volume (7,25,27,28), we examined the relationship between tangential work and the volume of resultant debris particles. Remarkably, we found that, at the debris level, these two quantities are related with a proportionality constant of 1/τ across the wide range of simulations performed in this work (Fig.…”
Section: Significancementioning
confidence: 99%
“…Our results show with statistical certainty that within the first tens of meters of slip faults smooth in both the slip‐parallel and slip‐perpendicular directions. The weak sensitivity to slip reported in Brodsky et al (), along with experimental evidence fault reroughening (e.g ; Badt et al, ), has led previous studies to suggest that fault roughness is a steady state between smoothing processes and reroughening (e.g., Brodsky et al, ; Candela et al, ; Fang & Dunham, ; Shervais & Kirkpatrick, ). However, we report an RMS‐smoothing exponent of 0.5 B (from equation , which is 5 times greater than that reported in Brodsky et al ().…”
Section: Discussionmentioning
confidence: 97%
“…Earlier frictional slip experiments on solid materials of different rheological properties demonstrated contrasting roughness on slip surfaces. Experiments with marble (Badt et al, ) and granite (Amitrano & Schmittbuhl, ) showed that the slip in the brittle regime produces greater roughness (Hurst exponent values >0.7), attributed to plow‐related processes, such as gouge formation and striations. Similar slip experiments on halite and limestone, in contrast, develop relatively smoother roughness (Hurst exponent < 0.5), where asperities cause plastic strain localization in their neighborhood (Renard et al, ; Sagy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing inclination of fractures to the compression direction results in a transformation from localized to global development of slickensides, characterized by one dimensional, multiordered wavy irregularities when θ = 60°. This effect of θ in promoting linear irregularities probably results from increasing normal stress on the shear surfaces (Badt et al, ; Davidesko et al, ). Larger compressive normal stresses favor the wavy mechanical instability in our models, which eventually produces linear geometry (details of the mechanics discussed later) to facilitate the slip motion.…”
Section: Laboratory Experimentsmentioning
confidence: 99%